2021
DOI: 10.3892/mmr.2021.11931
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg1 improves cognitive capability and affects the microbiota of large intestine of tree shrew model for Alzheimer's disease

Abstract: Ginsenoside Rg1 (Rg1) is traditional Chinese medicine with neuroprotective activity. Previous studies have demonstrated that Rg1 improves Alzheimer's disease (AD) and alters gut microbiology, but its mechanism remains to be elucidated, and thus far, its use in the treatment of AD has not been satisfactory. The present study investigated the improvement effects of Rg1 and its association with the microbiota of the large intestine. Following treatment with Rg1 in AD tree shrews, the treatment group demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…The increasing ratio of Aβ‐induced Bcl‐2/Bax can prevent cytochrome C transferring from mitochondrion to cytoplasm, reduce the cracking of Caspase‐9 and Cleaved‐caspase‐3, and further inhibit apoptosis caused by Aβ (Yang et al, 2019). Our previous studies (Guo et al, 2021) and others’ studies (Li et al, 2010; Shi et al, 2018) have shown that Rg1 has an anti‐apoptotic effect in AD, which was verified again in this study. MAP2 is considered as a specific index for neuronal dendritic.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The increasing ratio of Aβ‐induced Bcl‐2/Bax can prevent cytochrome C transferring from mitochondrion to cytoplasm, reduce the cracking of Caspase‐9 and Cleaved‐caspase‐3, and further inhibit apoptosis caused by Aβ (Yang et al, 2019). Our previous studies (Guo et al, 2021) and others’ studies (Li et al, 2010; Shi et al, 2018) have shown that Rg1 has an anti‐apoptotic effect in AD, which was verified again in this study. MAP2 is considered as a specific index for neuronal dendritic.…”
Section: Discussionsupporting
confidence: 88%
“…Ginsenoside is the main active ingredient of ginseng, and ginsenoside Rg1 (Rg1) is effective against AD in vivo or in vitro (Ardah et al, 2015;Liang et al, 2021;Nah et al, 2007). Our previous studies have shown that ginsenoside Rg1 improves cognitive function and reduces Aβ deposition and Tau phosphorylation in tree shrews with AD (Guo et al, 2021). The studies on the therapeutic effects and molecular mechanisms of Rg1 in AD tree shrews will provide further evidence for clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, traditional herbal medicine can induce changes in the microbiota in AD. The Ginsenoside Rg1, a traditional herbal medicine, can affect the microbiota of the large intestine by significantly reducing the abundance of gram-negative bacteria, Bacteroidetes , in the tree shrew model of AD [ 200 ]. Second, microbiota or fecal transplantation, which involves transplantation of microbiota in the feces of healthy humans into patients to balance the intestinal microflora, is an emerging therapeutic method for AD treatment [ 203 ].…”
Section: Gram-negative Bacteria and Their Lps As Therapeutic Targets In Admentioning
confidence: 99%
“…The pathogenesis of nervous system-related diseases is complex, and different signal pathways interact with each other. Studies have confirmed that Rg1 can treat AD by regulating the metabolism of intestinal flora [ 97 , 98 ]. However, there are few studies on Rg1 improving neurological diseases through intestinal flora.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in microbial composition may change signals in the central nervous system. In one study, Rg1 improved cognitive impairment by increasing the number of Lactobacillus salivarius in AD [ 97 ]. It has been shown that Rg1 changed the abundance of intestinal flora to improve AD, and that proteobacteria and verrucomicrobia are key microbiota [ 98 ] ( Figure 7 ).…”
Section: Targets Of Neurological Diseasesmentioning
confidence: 99%